Family dynamics and the psychosocial well-being of adolescents: A cross sectional study - Zaynab Ali Albar,; Ameera Ouda Alzahrani,; Nada Hamad Al Nasser,; Mohammad Furaih M Alenezi,; Khaled Farhan Farih Al-Anzi,; Nwaf Saliman Awwad Alshamari,; Salman Shayq Abbis Al-Shammari,; Naif Mesfer Abdulrahman Aloufi,; Abdullah Saad Salem Alsaedi,; Salem Mresheed Rasheed Alotaibi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Family dynamics play a pivotal role in shaping the psycho-social well-being of adolescents, particularly in Saudi Arabia (KSA), where cultural, social, and religious factors intertwine to influence the way families interact and raise their children. Significant emotional, cognitive, and social development characterize the adolescent years, and a young person's family environment greatly influences how they navigate these changes. The aim of the study:To assess family dynamics and the psycho-social well-being of in-school adolescents, with a view to determining the association between family dynamics and the psycho-social well-being of in-school adolescents. This provided a basis for planning family-oriented support services to improve the psycho-social health status of in-school adolescents. Study design: A descriptive cross-sectional design. Methods: Three hundred and thirty-five school-adolescents from public and privatesecondary schools in KSA were selected using the proportionate systematicrandom sampling technique. Data was collected with the Family Assessment Devicequestionnaire and Youth self-reported Pediatric Symptom Checklist and analyzed usingdescriptive and inferential statistics. Results: Findings showed that53.7%oftheparticipantshadunhealthyfamilydynamics while 16.0% had impaired psycho-social status. There is a significant negative association between family dynamics in problem solving dimension and psychosocial health status with a Beta coefficient (-1.120), Odd ratio=0.326 (95% CI 0.171 to 0.624). Conclusion: Majority of in-school adolescents had unhealthy family functioning pattern and one in six adolescents had impaired psychosocial health. There was a negative but significant association between the problem-solving dimension of family dynamics and psycho-social health. Community health professionals should carryout preventive interventions among parents and adolescents in the community with adequate attention toall the dimensions of family functioning.